FAKTOR-FAKTOR YANG MEMPENGARUHI KEBIJAKAN PENGUNGKAPAN TANGGUNGJAWAB SOSIAL DAN LINGKUNGAN PADA PERUSAHAAN YANG TERDAFTAR DI BURSA EFEK INDONESIA - Herlina, Herlina (Institut Agama Islam Bengkulu, 2016)
Factors That Influence The Policy Of Social Disclosure And Environmental Responsibility In Companies Listed On The Indonesia Stock Exchange. The aim of this study is to examine and provide empirical evidence about the factors that influence the policy of social disclosure and environmental responsibility in companies listed on the indonesia stock exchange, the observation period from 2007 until 2013. The sample obtained by 46 companies with 322 observations. The result of hypothesis test showed that the size of the company's significant impacts on the policy of social disclosure and environmental responsibility. The result of hypothesis test showed that the leverage had no significant impacts on the policy of social disclosure and environmental responsibility. The result of hypothesis test showed that the profitability had no significant impacts on the policy of social disclosure and environmental responsibility. The result of hypothesis test showed that the board of commissioners had no significant impact on the policy of social disclosure and environmental responsibility. The result of hypothesis test showed that the size of the company's significant impacts on the policy of social disclosure and environmental responsibility. The result of hypothesis test showed that managerial ownership had no significantly impacts on the policy of social disclosure and environmental responsibility. And The result of hypothesis test results showed that the age of firm had no significant impacts on the policy of social disclousure and environmental responsibility.Keyword : leverage, profitability, board of commissioners, size of company, managerial ownership, age of firm, CSR